2024
DOI: 10.47787/pasj.v2i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal fish species diversity and distribution in a medium-sized Afro-tropical river in the Lake Victoria Basin

Abstract: Despite significantly influencing fisheries characteristics of major global basins, medium-sized rivers such as Awach Kibuon remain the least studied. This study evaluated longitudinal fish species diversity, distribution, and environmental influence in Awach Kibuon River, Lake Victoria Basin, Kenya, to inform sustainable management of fisheries resources within the region. Nine sites located in different zones of the river were sampled monthly for eight months in 2019 and 2020. Fish samples were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
3
1
2
Order By: Relevance
“…This high electrical conductivity may be attributed to an increase in the concentration of salts as a result of degradation of organic matter and also due to high concentration of dissolved solids due to the discharge of high volume of untreated municipal, domestic and hospital wastes into the WWSP. However, the levels of electrical conductivity reported in the present study particularly River Kisat (329.51 -497.83S/cm) were lower than those reported by [18] (435.6 -795.2) and [28] (390.75 -839.65) (Table 2) but higher than what [27] reported in Awach Kibuon River. The results of EC observed in the present study were within the WHO standard limit of 1000 S/cm [37].…”
Section: Variation Of Physicochemical Water Quality Parameters In Riv...contrasting
confidence: 83%
See 4 more Smart Citations
“…This high electrical conductivity may be attributed to an increase in the concentration of salts as a result of degradation of organic matter and also due to high concentration of dissolved solids due to the discharge of high volume of untreated municipal, domestic and hospital wastes into the WWSP. However, the levels of electrical conductivity reported in the present study particularly River Kisat (329.51 -497.83S/cm) were lower than those reported by [18] (435.6 -795.2) and [28] (390.75 -839.65) (Table 2) but higher than what [27] reported in Awach Kibuon River. The results of EC observed in the present study were within the WHO standard limit of 1000 S/cm [37].…”
Section: Variation Of Physicochemical Water Quality Parameters In Riv...contrasting
confidence: 83%
“…The high TDS recorded could be due to the dissolved salts in the pre-treated wastewater. The levels of TDS obtained in this study were higher than that found by [19,21,27[ in rivers Mara, Vaigai (India) and Awach Kibuon. Similarly, TDS recorded in both River Kisat and Auji was higher compared to those reported in River Gudar (133.00 -179.00), a peri-urban river in Ethiopia [25] This suggests that there is an addition of organic matter and solid wastes into the studied rivers.…”
Section: Variation Of Physicochemical Water Quality Parameters In Riv...contrasting
confidence: 77%
See 3 more Smart Citations